Adolescents’ Difficulties in Performing the Five Daily Prayers in a Rural Muslim Community - Siti Aminah Hasibuan (Yayasan Tahfidzul Qur'an Al-Fawwaz, 2026)
This study analyzes adolescents’ difficulties in performing the five daily prayers in Parmainan Village, Hutaraja Tinggi District, Padang Lawas Regency, North Sumatra, Indonesia. The problem addressed in this study is the inconsistency between adolescents’ basic knowledge of prayer as an Islamic obligation and their daily practice of performing prayer regularly and on time. The study employed a descriptive qualitative approach with a case-study orientation. Data were collected through observation, semi-structured interviews with adolescents, parents, the village head, and religious/community leaders, as well as documentation of village and religious activities. Data were analyzed through data condensation, data display, and conclusion drawing, supported by source triangulation and persistent observation. The findings show that adolescents’ prayer practice remains inconsistent. Some adolescents perform prayer only at certain times, delay prayer because of smartphones, peer activities, fatigue, or household work, and pray mainly after parental reminders. The main difficulties appear in two stages: pre-prayer readiness and prayer performance. Pre-prayer difficulties include delaying ablution, weak time discipline, and difficulty disengaging from leisure or work activities. Prayer-performance difficulties include limited mastery of recitations and procedures, rushed movements, low concentration, and uncertainty about correct practice. These difficulties are shaped by personal motivation, procedural competence, parental modelling, peer norms, digital habits, and rural household demands. The study concludes that adolescents’ difficulty in establishing the five daily prayers should be understood as a layered religious-educational problem rather than merely as laziness or disobedience. Strengthening prayer discipline requires adaptive guidance, consistent parental modelling, peer-based religious support, digital habit management, and collaboration among families, schools, mosques, and village communities.